Mentoring and Socializing to Develop Gen Y and Gen Z Employees to Enhance Thailand’s Competitiveness - Techakana, Jusana; Patcharapinyopong, Nat (Asia Pacific Journal of Religions and Cultures, 2020)
The objectives of this research are: 1) to increase the competitiveness of Thailand in the global arena, 2) to find means to cultivate the right social values among cohorts of Gen V and Gen Z, 3) to employ mentoring and socializing to improve quality of human capital of Thailand, and 4) to identify factors that will develop Gen Y and Gen Z employees to be human resources with high quality. The method employed is in-depth interviews with key informants. The findings reveal that there are four important factors affecting young generations’ quality; they are 1) parents, 2) education, 3) social environments, and 4) mass communication. The four factors fail to develop Gen Y and Gen Z cohorts to be quality human capital; therefore, mentoring and socializing should be used to compensate for the failure. The authors propose a paradigm, entitled “SMART GEN” to develop Gen Y and Gen Z cohorts to become quality human resources that will enhance Thailand’s competitiveness. S stands for Sense of excellence, Sense of Contribution, and Social idiosyncrasy. M stands for Mindset, Mentality, and Multitasker, A stands for Attitudes, Achievement, and Adjustment. R stands for Respect, Relations, and Result-oriented. T stands for Teamwork, Trust, and Technology savvy. G stands for Gregarious, Governance, and Goal-oriented. E stands for Energy, Education, and Experience. N stands for Network, Negotiation, and Nationalism.